1998
DOI: 10.1023/a:1011904921318
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Human skin viability can be maintained for absorption studies. It is recommended that this system be used, and that heat-separation and skin freezing not be used, in absorption studies where skin viability and metabolism might be contributing factors to the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Culver et al reported that total estimated boron intake including both diet and environmental exposure had for the high-borax dust exposure group a mean daily boron intake of 27.90 mg/day [42]. In addition, it was determined that boron was absorbed by healthy skin only to a very limited extent [44], although absorption of boron that is present in liquid solution occurred in irritated skin [45]. Distribution of boric acid in human tissues is similar to that of animals.…”
Section: Boron Exposurementioning
confidence: 99%
“…Culver et al reported that total estimated boron intake including both diet and environmental exposure had for the high-borax dust exposure group a mean daily boron intake of 27.90 mg/day [42]. In addition, it was determined that boron was absorbed by healthy skin only to a very limited extent [44], although absorption of boron that is present in liquid solution occurred in irritated skin [45]. Distribution of boric acid in human tissues is similar to that of animals.…”
Section: Boron Exposurementioning
confidence: 99%
“…Three types of skin preparations can be distinguished: Epidermal skin sheets are prepared by heat, chemical or enzymatic separation from the dermis. They are quite fragile and do not possess high metabolic activity [24], although some remaining esterase activity may be present at quite high levels. Split thickness skin is prepared using a dermatome, a device that removes subcutaneous fat and some of the dermis to a specific depth.…”
Section: Ex Vivo Human Skin A) Sources Of Human Skinmentioning
confidence: 99%
“…Multiphoton excitation fluorescence microscopy found tissue structural damage due to frozen storage correlated to increasing permeation of caffeine, with damage most pronounced in skin stored at −80°C [17]. Regardless of any effects on barrier function, heat separation and skin freezing ought not to be used in permeation studies requiring skin viability and metabolism [32]. …”
Section: Introductionmentioning
confidence: 99%